Effect of sintering activators on the mineralization of α-Al2O3 during heat treatment of alumina; Refractories and Industrial Ceramics; Vol. 20, N 5-6 - Vereshchagin (Vereschagin, Vereshagin) V. I. Vladimir Ivanovich (1979, 1979)
Additions of Y2O3, MgO, and SrO are not only activators of the sintering of alumina but are also excellent mineralizers of corundum. The beneficial effect of these additions in the preparation of GA85 alumina for the production of a dense corundum ceramic is seen in the speeding up of processes by which the transitional forms of the aluminum oxide is transformed into α-Al2O3, the speeding up of the formation of its (α-Al2O3) structure, and in the increase in the apparent density while still retaining its activity for sintering